Dynamical Hybrid Observer for Pressure Swing Adsorption Processes. Issue 1 (July 2017) - Fakhroleslam, Mohammad; Boozarjomehry, Ramin Bozorgmehry; Fatemi, Shohreh; Fiore, Gabriella
Abstract: A dynamical hybrid observer is proposed for online reconstruction of the active mode and continuous states of Pressure Swing Adsorption (PSA) processes as an integral part of a hybrid control system. A mode observer is designed for estimation of the active mode, and the continuous spatial profiles are estimated by a Distributed and Decentralized Switching Kalman Filter. The proposed hybrid observer has been applied, in silico, for a two-bed, six-step PSA process. The active mode of the process along with the continuous spatial profiles of its adsorption beds have been estimated quite accurately based on very limited number of noise corrupted temperature and pressure measurements.